Kebijakan Perubahan Perbatasan Pemerintah Belgia dengan Belanda Tahun 2016 - Anandira Erawan, Putu Ayu Meisya; Putri, Penny Kurnia; Intan Prameswari, Anak Agung Ayu (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2021)
This research aims to describe factors of the Belgian Government to make border change policy with the Dutch Government in 2016 using qualitative methods. The location of the border area between Belgium and the Netherlands which is separated by the Meuse River has triggered various problems. In order to resolve these problems, Belgium is conducting negotiations on changing the border with the Netherlands. In this case, Belgium and the Netherlands are able to resolve problems regarding this border area peacefully. The researcher uses the concept of territoriality and water diplomacy to analyze the driving factors for the border change policy. This research perceives that the capability of law enforcement authorities, the idea of nexus governance through the management of the Meuse River, the implementation of human territoriality in the border area, and the potential to cooperate are the driving factors for Belgium to make border change with the Netherlands. Keywords: Belgium, Territoriality, Border Change, Water Diplomacy